GOOD FAITH AS LEGAL BENCHMARK FOR THE ALLOCATION OF LOSSES BY MUTUAL COMPANY - Widodo, Danu Kristian Ira (Faculty of Law, Parahyangan Catholic University, 2024)
Allocation of losses is a special scheme that can only be applied to mutual companies, legal entities that position policyholders as both insured parties and owners. The problem with the allocation of losses arises because, in its determination, policyholders are required to fulfill mutual obligations in the fiduciary realm as owners. On the other hand, the allocation of losses has implications for reducing the policyholder’s right to receive claims as agreed. This paper is a legal research study employing a statutory approach and a conceptual approach. The results of this study indicate that, for the allocation of losses to have legitimacy, it must align with fiduciary principles and be fair based on the terms of insurance agreements. The legal findings suggest that the principle of utmost good faith should be expanded in mutual companies to serve as an instrument of checks and balances by policyholders over management and aspects related to the fulfillment of agreements.